Desain Digitalisasi Jadwal dan Rute Kapal Feri Di Provinsi Sulawesi Tenggara - Hasmina Tari Mokui; Maudhy Satyadharma; Eko Wahyu Prasetyo; Zulfikar Putera (Borneo Engineering : Jurnal Teknik Sipil, 2023)
Ferry Ports play an important role in human life and the movement of goods in the Southeast Sulawesi Province region. However, there are still several obstacles for prospective service users in finding out port information, schedules and ferry crossing routes quickly and easily. To overcome this problem, researchers designed a web-based GIS application to search for the nearest port, port list, schedule information and ferry routes operating at all Ferry Ports managed by the Transportation Service. The research method was carried out by observing to collect data and then analyzing application needs which resulted in application design and design which was defined by Use Case Diagrams, Entity Relationship Diagrams (ERD) and application interface displays. It is hoped that the final results of this research will produce an application that is user friendly and can assist the needs of prospective service users in finding information on ferry schedules and routes easily, thereby having an impact on increasing efficiency, comfort and passenger satisfaction as well as reducing uncertainty in finding information related to schedules and routes. the ferry. It is certainly hoped that the recommendations of this research will enable the Southeast Sulawesi Provincial Transportation Service to develop a better Information Search and Ferry Route Application for ease and optimal organization of ferry transportation to encourage increased satisfaction of service users.